2020
DOI: 10.1186/s40478-020-01027-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of diverse low-grade neuroepithelial tumors with FGFR1 alterations reveals a distinct molecular signature of rosette-forming glioneuronal tumor

Abstract: The FGFR1 gene encoding fibroblast growth factor receptor 1 has emerged as a frequently altered oncogene in the pathogenesis of multiple low-grade neuroepithelial tumor (LGNET) subtypes including pilocytic astrocytoma, dysembryoplastic neuroepithelial tumor (DNT), rosette-forming glioneuronal tumor (RGNT), and extraventricular neurocytoma (EVN). These activating FGFR1 alterations in LGNET can include tandem duplication of the exons encoding the intracellular tyrosine kinase domain, in-frame gene fusions most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…Despite its nomenclature, multiple cases of focal, circumscribed parenchymal tumor have resolved to diffuse leptomeningeal glioneuronal tumor on methylome analysis [ 90 ], making the classification of this entity unclear. Epigenetic analysis is further aiding the delineation of rosette-forming glioneuronal tumor from PA and other low grade neuroepithelial tumors with overlapping genomic signatures, with recent description of FGFR1 p.N546 or p.K656 mutation with PIK3CA or PIK3R1 appearing to represent a molecular signature specific to rosette-forming glioneuronal tumor [ 42 ].…”
Section: High Risk Features Of Pamentioning
confidence: 99%
“…Despite its nomenclature, multiple cases of focal, circumscribed parenchymal tumor have resolved to diffuse leptomeningeal glioneuronal tumor on methylome analysis [ 90 ], making the classification of this entity unclear. Epigenetic analysis is further aiding the delineation of rosette-forming glioneuronal tumor from PA and other low grade neuroepithelial tumors with overlapping genomic signatures, with recent description of FGFR1 p.N546 or p.K656 mutation with PIK3CA or PIK3R1 appearing to represent a molecular signature specific to rosette-forming glioneuronal tumor [ 42 ].…”
Section: High Risk Features Of Pamentioning
confidence: 99%
“…Among the 1155 prospective samples tested, Capper et al ( 35 ) reported 88% of classified cases (with calibrated scores of at least 0.9). In the same way, Jaunmuktane et al ( 32 ) reported a rate of 56% of CNS tumors matching a known MC (with calibrated scores of at least 0.84), while Lucas et al ( 44 ) reported 40% of match cases (with calibrated scores of at least 0.9) in a cohort of low-grade neuroepithelial tumors. Moreover, Karimi et al ( 43 ) reported that 84% of the cases tested with this tool had a clinically significant change in the histopathological diagnosis, with 15% of all those cases associated with a change in clinical decision-making for the patient.…”
Section: Discussionmentioning
confidence: 89%
“…A subset of RGNT may lack this biphasic appearance and contain a predominantly oligodendroglioma-like or PA-like histology. 56 , 57 Indeed, 3 of 10 methylation-defined RGNT in a recent report were initially characterized as “low-grade oligodendroglial tumor NOS (not otherwise specified)” and lacked the characteristic neurocytic rosettes. 57 Genetically, RGNT are among the FGFR1 -altrered spectrum of LGG/LGNT and harbor either an FGFR1 p.N546 or p.K656 mutation, identified in 40 of 40 methylation-defined cases to date.…”
Section: Glioneuronal Tumorsmentioning
confidence: 99%